Pengaruh Media Sosial, Aksebilitas dan Fasilitas Islami terhadap Minat Berkunjung Ke Wisata Pulau Larea-Rea Kabupaten Sinjai dengan Kepercayaan sebagai Variabel Moderating - Lisda, Lisda; Sofyan, A. Syathir; Katman, Muhammad Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this study is to evaluate the impact of social media, accessibility, and interest in visiting Islamic facilities. Larea-Rea Island Tourism, Sinjai Regency with Having faith is a moderating factor. In this research, the sample is the people of Sinjai district. A quantitative technique with a descriptive methodology is the research method employed. In this study, questionnaires, interviews, and documentation were utilized as primary and secondary data sources gather information. Analysis of research was conducted using the data processing tool SmartPLS 4.0. Regression analysis shows that interest in visiting (Y) Larea-rea island tourism is positively and significantly influenced by social media (X1), accessibility (X2), and Islamic facilities (X3). Moreover, the impact of social media on visiting interest might be strengthened or moderated by the trust variable (Z). Have faith can moderate (strengthen) the accessibility variable on visiting interest. However, it cannot moderate (strengthen) Islamic facilities on interest in visiting Larea-rea island tourism with confidence.